Rekayasa Mesin Pemilah dan Penghancur Sampah Otomatis dengan Sistem Kendali Kontrol Sederhana pada Skala Internal Politeknik Negeri Batam - Fedia Restu (JURNAL INTEGRASI, 2013)
Along with the development of the times, the problem posed increasingly diverse. One of them is the problem of garbage that hard pressed to treatment be it organic or nonorganic. Until recently the issue has yet to be addressed optimally and professionally. Waste Shredder architecture aims to create garbage recyclers tool, so the trash can be recycled into useful items and have economic value. To focus the creation of this shredder, then the manufacture is limited only in the manufacture of organic waste shredder and non-organic. The architecture is expected to work well and can destroy waste into granules, granules with as cheaper manufacturing costs. The expectations of this research, the garbage processing machine independent materialize by Batam State Polytechnic as well as get a healthy environment hygiene and Techno- preneurship in the field of the environment.